Interaction of the GCKR and A1CF loci with alcohol consumption to influence the risk of gout - Humaira Rasheed; Lisa K. Stamp; Nicola Dalbeth; Tony R. Merriman (Arthritis Research & Therapy, 2017)
Abstract Background Some gout-associated loci interact with dietary exposures to influence outcome. The aim of this study was to systematically investigate interactions between alcohol exposure and urate-associated loci in gout. Methods A total of 2792 New Zealand European and Polynesian (Māori or Pacific) people with or without gout were genotyped for 29 urate-associated genetic variants and tested for a departure from multiplicative interaction with alcohol exposure in the risk of gout. Publicly available data from 6892 European subjects were used to test for a departure from multiplicative interaction between specific loci and alcohol exposure for the risk of hyperuricemia (HU). Multivariate adjusted logistic and linear regression was done, including an interaction term. Results Interaction of any alcohol exposure with GCKR (rs780094) and A1CF (rs10821905) influenced the risk of gout in Europeans (interaction term 0.28, P = 1.5 × 10−4; interaction term 0.29, P = 1.4 × 10−4, respectively). At A1CF, alcohol exposure suppressed the gout risk conferred by the A-positive genotype. At GCKR, alcohol exposure eliminated the genetic effect on gout. In the Polynesian sample set, there was no experiment-wide evidence for interaction with alcohol in the risk of gout (all P > 8.6 × 10−4). However, at GCKR, there was nominal evidence for an interaction in a direction consistent the European observation (interaction term 0.62, P = 0.05). There was no evidence for an interaction of A1CF or GCKR with alcohol exposure in determining HU. Conclusions These data support the hypothesis that alcohol influences the risk of gout via glucose and apolipoprotein metabolism. In the absence of alcohol exposure, genetic variants in the GCKR and A1CF genes have a stronger role in gout.